The IL-18, IL-12, and IFN-γ expression in HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) patients, HTLV-1 carriers, and healthy subjects - Bidkhori, Hamid Reza; Hedayati-Moghaddam, Mohammad Reza; Mosavat, Arman; Valizadeh, Narges; Tadayon, Mohsen; Ahmadi Ghezeldasht, Sanaz; Rafatpanah, Houshang; Rezaee, Seyed Abdolrahim (Journal of neurovirology, 2020)
Interleukin (IL)-12, IL-18, and interferon gamma (IFN-γ) can induce Th1-inflammatory responses in favor of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) manifestation. In this study, the gene expression and plasma levels of these cytokines were evaluated. The peripheral blood mononuclear cells (PBMCs) in 20 HAM/TSP patients, 21 asymptomatic carriers (ACs), and 21 healthy subjects (HSs) were assessed for the expression of IL-18 , IL-12 , and IFN-γ , using qRT-PCR. The plasma level of IL-18 and IFN-γ were measured by an ELISA method. The mean of HTLV-1 proviral load (PVL) in the HAM/TSPs was 1846.59 ± 273.25 and higher than ACs at 719.58 ± 150.72 ( p = 0.001). The IL-12 was considerably expressed only in nine ACs, five HAM/TSPs, and all HSs. Furthermore, the gene expression and plasma levels of IL-18 were lower in the HTLV-1-positive group than the control group ( p = 0.001 and 0.012, respectively); however, there was no significant difference between the ACs and HAM/TSPs. The IFN-γ level was higher in the HTLV-1-positive group ( p < 0.001) than HSs. Although there were no correlation between plasma levels of IL-18 and IFN-γ with PVL in the ACs, a positive correlation was observed between plasma IL-18 levels and PVL ( r = 0.654, p = 0.002). The highest levels of IFN-γ were observed in the HAM/TSPs which has a significant correlation with HTLV-1- HBZ ( r = 0.387, p = 0.05) but not with Tax . However, no significant correlation was found between PVL and proinflammatory pattern. Apart from the IFN-γ as a lymphokine, as a host factor, and HTLV-1- HBZ , as a viral agent, the other proinflammatory monokines or HTLV-1 factors are among the less-effective agents in the maintenance of HAM/TSP.